Entrepreneurship Education as a Panacea to a Depressed Economy: Nigeria in Perspective - Ologunowa, Christopher Sunday; Itodo, Christiana Ijakuwa (NIU Journal of Humanities, 2017)
It is evidently clear that entrepreneurship education involves the process of acquisition of knowledge and skills by both students and trainees on how to develop ideas that would be transformed into business venture. People and nations are what they are today because of the nature and type of education they are exposed to as Entrepreneurship education  makes it possible for a country to have highly intelligent and creative citizens who always keep improving the living conditions of the general citizenry and solve problem that may emanate from society. No wonder entrepreneurship education has been embraced by almost all the developed and developing countries. Nigeria today is passing through a lot of changes in virtually every field of her citizensâ€™ endeavour. These changes are no doubt, more on economic development. It is understandable that even some developed states of the world had experienced economic depression in the past and applied entrepreneurship as a catalyst for reviving the economy.  So, entrepreneurship can be seen as a tool that facilitates economic, social, political and technological advancement and diversification in all human societies. This therefore places heavy responsibilities on managers of educational institutions in Nigeria as this objective can only be realized and sustained through an efficient educational system that could impart the relevant skills, knowledge, attitudes and values to the students. It is evidently clear today that virtually almost all graduates of tertiary institutions are not gainfully employed either by sells or government. This ugly situation can be addressed by adequate entrepreneurship education by reducing the number of unemployed in the societies. To critically understand the phenomenon of entrepreneurship, this paper takes a general global look at the nature of entrepreneurship, entrepreneurship education and discusses the role it plays, problem of entrepreneurship with particular references to the role of the government and educational institutions in Nigeria. In so doing, the author employs secondary method of generating data. In precise, the paper establishes the link between entrepreneurship education and sustainable development. Keywords: entrepreneur, entrepreneurship education depressed economy